2016
DOI: 10.1111/medu.13117
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of assessment and intervention strategies for effective clinical communication in culturally and linguistically diverse students

Abstract: The development of effective assessment and intervention programmes should have an integrated design and include specific outcome measures to increase educational impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…Further, perceptions of teachers at other universities about the desirability of screening the communication skills of students could be explored. However, the themes discussed in this study reflect those described in the literature, including both the perceptions of university teachers about student skills and their desire to develop appropriate strategies to support students (Attrill, Lincoln, and McAllister 2012, Attrill, Lincoln, and McAllister 2016, Chan, Purcell and Power 2016, Parry and Brown 2009, Rider, Hinrichs and Lown 2006, Shapiro, Ogletree, and Dale Brotherton 2002, Stupans et al 2010, Wagner, Liston, and Miller 2011.…”
Section: Recommendationsmentioning
confidence: 61%
See 1 more Smart Citation
“…Further, perceptions of teachers at other universities about the desirability of screening the communication skills of students could be explored. However, the themes discussed in this study reflect those described in the literature, including both the perceptions of university teachers about student skills and their desire to develop appropriate strategies to support students (Attrill, Lincoln, and McAllister 2012, Attrill, Lincoln, and McAllister 2016, Chan, Purcell and Power 2016, Parry and Brown 2009, Rider, Hinrichs and Lown 2006, Shapiro, Ogletree, and Dale Brotherton 2002, Stupans et al 2010, Wagner, Liston, and Miller 2011.…”
Section: Recommendationsmentioning
confidence: 61%
“…There is a lack of literature discussing which underlying communication skills are required to successfully develop the clinical competencies required for effective practice. A recent systematic review of communication assessments for university students and graduates (Chan, Purcell and Power 2016) indicated that most research to date has examined the clinical communication skills of predominantly medical and nursing students using standardised patients and Likert-based rating scales. They also note some less frequent use of single measures of language, including the Australian Tertiary English Test or the Woodcock Language Proficiency Test, to assess clinical communication, and list the detailed communication skills assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Is represents professional identity. 29,30 Study outcomes were classified using Kirkpatrick's Hierarchy, which evaluates the impact of medical education research [31][32][33] using four levels: Level 1 (participation), Level 2a (attitudes and perceptions) and Level 2b (knowledge and skills), Level 3 (behavioral change), and Level 4a (organization practice) and 4b (patient benefits). 31 Assessment instrument reliability and validity coefficients reported in the studies were interpreted as poor (<0.5), moderate (0.5 to 0.75), good (0.75 to 0.90), and excellent (>0.90).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students with a native language other than that of the majority of their peers, might face an additional challenge when it comes to communication skills. Language competence is described as a prerequisite for good communication skills [ 4 ].…”
Section: Introductionmentioning
confidence: 99%